Kajian Sumberdaya Lobster yang didaratkan di Kota Sorong, Papua Barat - misbah Sururi; Silvester Simau; Sudirman Sudirman; Endang Gunaisah; Sepri Sumbung; Muh Suryono; Samsul Muhamad; Abdul Gofir (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2016)
This paper describes the state of lobster resource which landed in Sorong, including species, fishing season, and the analysis of weight-length relationship. The measurements were carried out by using randomized sampling in three (3) lobster shelter in Sorong from September - November 2015. Total of 1.316 lobster were observed during this research. The data observed were species, carapace length (mm), weight (g) and gender. The aspects of fishing technique, season, marketing and lobster types were analyzed by using descriptive analysis, whereas the measurement data was analyzed by using linear allometrik model to see the weight-length relationship with the equation of W = a Lb . The result showed that there are six types of lobster which landed in Sorong namely are; Panulirus ornatus, P. versicolor, P. longipes, P homarus, P penicillatus, and Thenus orientalis. Fishing season was carried the whole year which consists of the peak season (June, November, December), middle season (March-July, September-October) and bad season (August, January, February). The whole lobster observed in this research have negative allometric growth pattern which indicates that the lobster are in growth stage.